2022
DOI: 10.1021/acsaem.2c02047
|View full text |Cite
|
Sign up to set email alerts
|

Lithium-Ion Battery Degradation: Measuring Rapid Loss of Active Silicon in Silicon–Graphite Composite Electrodes

Abstract: To increase the specific energy of commercial lithium-ion batteries, silicon is often blended into the graphite negative electrode. However, due to large volumetric expansion of silicon upon lithiation, these silicon–graphite (Si–Gr) composites are prone to faster rates of degradation than conventional graphite electrodes. Understanding the effect of this difference is key to controlling degradation and improving cell lifetimes. Here, the effects of state-of-charge and temperature on the aging of a commercial … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…These results also show that SiOx electrochemical activity is decreased for the cells that are cycled down to 0% SoC such as R0-50, H0-50, R0-100, and H0-100 (Figure 3 b, c, f, g). This trend is expected as SiOx is known to degrade at cell potentials below 50% SoC [79]. On the contrary, the positive electrode degradation is anticipated at potentials corresponding to ≥50% SoC due to lower stability of the positive electrode upon delithiation [80].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…These results also show that SiOx electrochemical activity is decreased for the cells that are cycled down to 0% SoC such as R0-50, H0-50, R0-100, and H0-100 (Figure 3 b, c, f, g). This trend is expected as SiOx is known to degrade at cell potentials below 50% SoC [79]. On the contrary, the positive electrode degradation is anticipated at potentials corresponding to ≥50% SoC due to lower stability of the positive electrode upon delithiation [80].…”
Section: Discussionmentioning
confidence: 95%
“…𝑄 Si = 𝑄 𝑑 − 𝑄 N3 − 𝜃 𝑐 ⋅ 𝑄 Gr The necessary assumption in this estimation is that both the silicon and graphite are fully delithiated following the 0.1C step to 1.5 V. Effectively, this resolves the silicon amount that is kinetically available, which may be somewhat less than the total silicon content determined by other techniques. In spirit, this method of separating the silicon contribution is the same as can be done with fitting the open circuit potential for blended electrodes [79]. However, this manual algebraic calculation provides simplified, quick quantification in concert with the analysis of the differential voltage profiles.…”
Section: Detailed Analysis Of the Degradation Of The Negative Electrodementioning
confidence: 99%
“…This expansion leads to the decomposition and reconstruction of the SEI layer, thereby consuming more lithium. 9,48,50,51 At a higher SoC range, the graphite dominates the aging behavior, which can be seen by the similar capacity loss regardless of SiOx content in the cells.…”
Section: ιιmentioning
confidence: 94%
“…[52] Kirkaldy et al observed that the LAM of active Si was greater than that of graphite at low SOC and high temperatures. [62] Zhang et al discovered that the dissolution of transition metals (TMs) was more detrimental to Si than to graphite. [63] The LAM PE is highly dependent on different cathode chemistries.…”
Section: Loss Of Active Materials (Lam)mentioning
confidence: 99%